Decomposing differences in depressive symptoms between older rural-to-urban migrant workers and their counterparts in mainland China - Wei Yang; Dan Li; Jianmin Gao; Xiaojuan Zhou; Fuzhen Li (BMC, 2020)
Abstract Background There has been an increase in older rural-to-urban migrant workers (aged 50 and above) in mainland China, little known about their depressive symptoms. The aim of this study was to identify depressive symptoms among older rural-to-urban migrant workers, as well as explored the factors leading to differences in depressive symptoms between older rural-to-urban migrant workers and their rural counterparts (older rural dwellers) and urban counterparts (older urban residents) in mainland China. The results provided a comprehensive understanding of the depressive symptoms of older rural-to-urban migrant workers, and had great significance for improving the depressive symptoms for this vulnerable group. Methods Data were derived from the China Health and Retirement Longitudinal Study (CHARLS) conducted in 2015, and coarsened exact matching (CEM) method was employed to control confounding factors. This study employed a Chinese version 10-item short form of the Center for Epidemiologic Studies-Depression Scale (CES-D 10) to measure depressive symptoms, and used the Social-Ecological Model as a framework to explore influential factors related to depressive symptoms. Specifically, the approach of Fairlie's decomposition was used to parse out differences into observed and unobserved components. Results After matching, our findings indicated that the prevalence of depressive symptoms in older rural-to-urban migrant workers was lower than older rural dwellers; and the prevalence of depressive symptoms in older rural-to-urban migrant workers was higher than older urban residents. Fairlie's decomposition analysis indicated that type of in-house shower, sleeping time at night and ill in the last month were proved to be major contributors to the differences in depressive symptoms between older rural-to-urban migrant workers and older rural dwellers; self-reported health and sleeping time at night were proved to be major contributors to the differences in depressive symptoms between older rural-to-urban migrant workers and older urban residents. Conclusions Differences in depressive symptoms between older rural-to-urban migrant workers and their rural and urban counterparts did exist. Our findings contributed to a more reliable understanding in depressive symptoms among older rural-to-urban migrant workers. Our findings would be of referential significance for improving older rural-to-urban migrant workers' depressive symptoms.